Gender aspects in allergies of pets – A secondary publication and update - Ina Herrmann; Lukas Einhorn; Lucia Panakova (World Allergy Organization Journal, 2017)
Abstract Allergies need not only affect humans; this multifactorial and complex disease can also affect animals. Comparative allergology investigates the many similarities between the pathogenesis, clinics, diagnosis, and therapy of the disorders in humans and pet animals. In contrast to human allergy research, the veterinary field lacks access to a central database, which means there are no cohort studies published. This limits not only the research on breed and regional differences in allergies, but also further studies on the impact of gender in allergies of domestic animals. Moreover, domestic cats, dogs and male horses are castrated in most cases, which neutralises any effects of sexual hormones. In this review article a few interesting findings regarding gender aspects in companion animals were extracted from current literature. In summary, there is a lack of data on gender effects on allergies in cats, dogs or horses.